Amphetamine- and Opioid-Affected Births: Incidence, Outcomes, and Costs, United States, 2004–2015 - Admon, Lindsay K. (Am J Public Health, 2019)
Objectives. To estimate trends in incidence, outcomes, and costs among hospital deliveries related to amphetamines and opioids. Methods. We analyzed 2004-to-2015 data from the National Inpatient Sample, a nationally representative sample of hospital discharges in the United States compiled by the Healthcare Cost and Utilization Project, by using a repeated cross-sectional design. We estimated the incidence of hospital deliveries related to maternal amphetamine or opioid use with weighted logistic regression. We measured clinical outcomes and costs with weighted multivariable logistic regression and generalized linear models. Results. Amphetamine- and opioid-related deliveries increased disproportionately across rural compared with urban counties in 3 of 4 census regions between 2008 to 2009 and 2014 to 2015. By 2014 to 2015, amphetamine use was identified among approximately 1% of deliveries in the rural West, which was higher than the opioid-use incidence in most regions. Compared with opioid-related and other hospital deliveries, amphetamine-related deliveries were associated with higher incidence of preeclampsia, preterm delivery, and severe maternal morbidity and mortality. Conclusions. Increasing incidence of amphetamine and opioid use among delivering women and associated adverse gestational outcomes indicate that amphetamine and opioid use affecting birth represent worsening public health crises.